Determinants of R&D offshoring - Gavin Murphy; Iulia Siedschlag (European Commission, Joint Research Centre (JRC), 2015)
We analyse determinants of an enterprise's decision to offshore R&D activities using a novel data set for enterprises in Ireland over the period 2001-2006. Our results suggest that, on average, other things equal, enterprises integrated in international production and innovation networks, and enterprises which used information and communication technologies (ICT) more intensively were more likely to offshore R&D. Furthermore, characteristics of the import source region had an important influence on enterprise offshoring behaviour, with offshoring to regions outside of the advanced European Union's economies being less likely.
Keywords: F14; F23; D22; 330; Global production and innovation networks; International sourcing of R&D.